2013
DOI: 10.1097/ta.0b013e318299d909
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of novel hemostatic dressings with QuikClot combat gauze in a standardized swine model of uncontrolled hemorrhage

Abstract: These results suggest that the novel hemostatic devices perform at least as well as the current Committee on Tactical Combat Casualty Care standard for point-of-injury hemorrhage control. Despite their different compositions and sizes, the lack of clear superiority of any agent suggests that contemporary hemostatic dressing technology has potentially reached a plateau for efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 11 publications
3
56
0
Order By: Relevance
“…The effectiveness and usefulness of QuikClot gauze and Celox gauze in the rapid control of massive bleeding has been repeatedly confirmed in experimental studies (Paltrinieri et al 2008), in hospital settings and on the battlefield in direct warfare (Devlin et al 2011, Rall et al 2013. Our study demonstrated the efficacy of both dressings in the control of bleeding from the injured femoral artery.…”
Section: Discussionsupporting
confidence: 49%
“…The effectiveness and usefulness of QuikClot gauze and Celox gauze in the rapid control of massive bleeding has been repeatedly confirmed in experimental studies (Paltrinieri et al 2008), in hospital settings and on the battlefield in direct warfare (Devlin et al 2011, Rall et al 2013. Our study demonstrated the efficacy of both dressings in the control of bleeding from the injured femoral artery.…”
Section: Discussionsupporting
confidence: 49%
“…other products have also been developed. While these agents have demonstrated superior efficacy in compressible hemorrhage control compared to regular gauze (10), no one alternative has shown clear superiority over others (11). Presently, the most frequently used hemostatic dressing is the combat Gauze ® , which combines surgical gauze with the aluminosilicate kaolin.…”
Section: Hemostatic Dressingsmentioning
confidence: 99%
“…Hemostatic agents are used in both military and civilian medicine during intervention and rescue operations (Ran et al 2010, Travers et al 2012. The effectiveness of hemostatic dressings such as QuikClot, Chitoauze and Celox gauze has been used in combat and in laboratory analyses, but there is still scanty information (Rall et al 2013). …”
Section: Introductionmentioning
confidence: 99%